1999
DOI: 10.1001/archotol.125.1.21
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Treatment of Hemangiomas in Children With Interferon Alfa-2a

Abstract: In pediatric patients with massive or life-threatening hemangiomas, interferon alfa-2a therapy is an effective treatment option. However, neurological evaluation before and during therapy with interferon alfa-2a should be performed owing to a significant incidence of neurological abnormalities (28%). Although all children with neurological findings demonstrated neurological recovery after discontinuation of therapy, we have changed our protocol and now more gradually increase the dosage of interferon alfa-2a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
17

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 34 publications
3
70
0
17
Order By: Relevance
“…Although some have reported response rates of up to 90% in steroid-resistant lesions, the effect is gradual in onset, and rebound can occur on discontinuation. 254 Up to 20% of children treated with interferon-a appear to develop spastic diplegia. 255 This complication tends to occur later in the treatment course and may be irreversible.…”
Section: Interferon-amentioning
confidence: 99%
“…Although some have reported response rates of up to 90% in steroid-resistant lesions, the effect is gradual in onset, and rebound can occur on discontinuation. 254 Up to 20% of children treated with interferon-a appear to develop spastic diplegia. 255 This complication tends to occur later in the treatment course and may be irreversible.…”
Section: Interferon-amentioning
confidence: 99%
“…21 In cases of steroid-resistant lesions, second-line therapy with interferon-á and vincristine had an almost 100% success rate, but adverse reactions ranged from minor to very severe. 8,22 In 2008, Léauté-Labrèze et al 23 reported that propranolol administered for decreased cardiac output in a child with a capillary haemangioma led to permanent regression of the lesion. This finding was confirmed in another report of 11 children treated with propranolol for capillary haemangioma.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, not all hemangiomas respond to these drugs and neurological toxicity has been associated with interferon-␣ administration. 5,6 The recent demonstration of ectopic expression of type 3 iodothyronine deiodinase in hemangioma, which in at least one child caused hypothyroidism, 7 underscores the need for novel therapy.…”
mentioning
confidence: 99%